Uji Cemaran Bakteri E. coli dan Salmonella sp. Pada Daging Sapi Di Pasar Tradisional Kecamatan Hamparan Perak - Silvi Eka Putri; Kurniawan Sinaga; Alfath Rusdhi (Journal of Pharmaceutical and Sciences, 2023)
Indonesian people prefer beef as a source of meat. More production and focus on high quality beef to meet the increasing demand for beef. The purpose of this study was to ascertain whether beef at the local market in Hamparan Perak District was contaminated with Salmonella sp. and E. coli. This research was conducted in January and February 2023 and is a descriptive study. Five samples of beef sold at the Klumpang Inpres Market, Hamparan Perak District, were used in this study. The findings revealed 18 bacterial isolates, most of which were round with intact edges, most of which were flat in height, and almost all of which were white. Seller 3 has the largest total number of microorganisms with a sample number of PS3 4.8 106 CFU / g, while seller 5 has the lowest number of PS5 samples 1.3 106 CFU / g. Contamination test results for Salmonella sp. and E.coli showed that all meat samples tested positive for Salmonella sp. and E. coli. A total of 4 isolates of gram-positive bacteria with purple color were found in the findings of bacterial staining, while there were 14 isolates of gram-negative bacteria with red and pink colors.